Commonly used UV filter toxicity on biological functions: review of last decade studies. (15th January 2013) - Gilbert, E.; Pirot, F.; Bertholle, V.; Roussel, L.; Falson, F.; Padois, K.
Synopsis Sunscreens provide broad‐spectrum UV skin protection and contain more often UV filter combinations. Their efficacy reducing skin photo carcinogenesis and photo ageing is widely documented. However, there are many concerns about UV filter safety. Organic UV filters were the first targeted by scientist concerns, as they were showed to trigger skin allergic reactions. Inorganic UV filters were then at the heart of scientist debate especially because of their nanometric size. Over the last years, many studies have been published tending to highlight that organic as well as inorganic UV filters could lead to variable side effects after sunscreen application. However, these studies are still very controversial due to different experimental conditions and models. This review reveals that complementary studies using standardized methods are mandatory before ascertaining that UV filters threaten human health.